Leitura popular da Bíblia como prática de educação para a consciência crítica: a experiência do CEBI em Mossoró (décadas de 80 e 90). - Nascimento, Zélia Cristina Pedrosa do (2024)
Popular Bible Reading (LPB), as carried out by the Center for Biblical Studies (CEBI), is an educational practice that contributes to the formation of critical consciousness. The veracity of this hypothesis will be demonstrated in our work based on the experience lived in the Diocese of Mossoró of the Roman Catholic Church in the 80s and 90s of the 20th century. We start with a historical review, remembering the birth of CEBI in partnership and communion with other experiences of liberating education and action that emerged in Brazil from the 1960s onwards and contributed to the formation of several popular movements. Along the way, the close relationship between popular reading of the Bible and Popular Education stands out, based on their mutual influences, differentiations and inspirations in the See, Judge and Act method. As an educational and mystical process, Popular Reading of the Bible generated adherences and transformations in the understanding of the world and in the political and professional options of several people who built the LPB in the Diocese of Mossoró, the main one was the creation of a new critical consciousness, as will be demonstrated from the subjects’ statements. This is a revolutionary experience that can illuminate the current Brazilian religious situation marked by polarization and fundamentalism, as the Popular Reading of the Bible awakens to action in reality and a commitment to the impoverished as an ethical requirement of faith in Jesus. Religion always has a political presence in society, whether revolutionary or conservative. The way we read the world and the Word of God will define our options.